ANALISA PENGARUH BUDAYA ORGANISASI TERHADAP MOTIVASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Kusumawati, Dara (Prodi Magister Manajemen FE-UST, 2018)
This research is to know how far the relationship between organizational culture to employee motivation with job satisfaction as intervening variable in performing daily tasks. Data type is primary data. Methods of data collection using questionnaires tested by instrument test on the level of validity and reliability. Respondents of SMK NU Kunduran Blora staff with a total sample of 32 respondents.The method used to analyze the data is Descriptive Analysis, Normality Test, Hypothesis Test consisting of Coefficient of Determination (R2), Test F, Test t.Based on the results of data processing and analysis has been done, organizational culture has a positive and significant impact on job satisfaction. Organizational culture has a significant influence on motivation. Job satisfaction has an insignificant influence (small effect) on Motivation. The indirect effect of organizational culture on motivation through job satisfaction is smaller than the direct influence of organizational culture on motivation. This shows that job satisfaction is not able to be an intervening variable between organizational culture and motivation.Keywords: Organizational Culture, Job Satisfaction, Motivation